Endometrial polyps: diagnosis and treatment options - a review of literature - Raz, Nili; Feinmesser, Larissa; Moore, Omer; Haimovich, Sergio (Minimally invasive therapy and allied technologies, 2021)
Endometrial polyps (EPs) are a common gynecologic condition, associated with abnormal uterine bleeding (AUB), infertility, and premalignant and malignant conditions. Technologies for diagnosis and treatment of EPs are constantly evolving. We aim to provide an updated review on diagnosis and management options for patients with EPs. We conducted an electronic search in databases including MEDLINE, PubMed, Cochrane Central Register and others. We included 68 publications regarding EPs, their clinical burden, diagnostic modalities, treatment options and new technologies. Transvaginal ultrasound (TVS) is the common modality for EP detection and color doppler increases its diagnostic accuracy. Dilation and curettage (D&C) should be avoided for diagnosis and treatment of EPs. Hysteroscopy shows high diagnostic value in EPs and allows for both histological diagnosis and effective treatment. Office hysteroscopy and see and treat hysteroscopy without anesthesia is feasible and safe for EP diagnosis and treatment, gaining more trained surgeons globally. Effective and safe technological tools for EP resection include Laser, resectoscopes, morcellators, MyoSure, Truclear and scissors\graspers. EPs are safely and effectively diagnosed and treated with the hysteroscopic tools reviewed in this article. More research is needed to define the best treatment modality.